2016
DOI: 10.17310/ntj.2016.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Tax Incidence and Rental Housing: A Survey and Critique of Research

Abstract: A longstanding question in economic research has been the incidence of taxes on land and on developed parcels of real estate. In the case of agricultural land, is it the landlord or the tenant farmer who ultimately pays a land tax? In the case of urban rental housing, is it the apartment owner or the renter who pays the property tax? This paper surveys the modern economic literature that has addressed these questions. Although some progress has been made in providing answers, this paper argues that several key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…The previous literature has offered a wide range of estimates for the pass-through of property taxes on rents: Orr (1968Orr ( , 1970Orr ( , 1972, Heinberg and Oates (1970), Hyman and Pasour (1973), Dusansky et al (1981), and Carroll and Yinger (1994) estimate that between 0-115 percent of the tax is shifted onto renters. Our results also show the dynamics of the property tax incidence in the short and medium run, which is particularly important for housing markets (England, 2016). We find that property tax increases lead to lower house prices, which is evidence of capitalization into house values (Palmon andSmith, 1998, de Bartolomé andRosenthal, 1999).…”
Section: Introductionsupporting
confidence: 54%
“…The previous literature has offered a wide range of estimates for the pass-through of property taxes on rents: Orr (1968Orr ( , 1970Orr ( , 1972, Heinberg and Oates (1970), Hyman and Pasour (1973), Dusansky et al (1981), and Carroll and Yinger (1994) estimate that between 0-115 percent of the tax is shifted onto renters. Our results also show the dynamics of the property tax incidence in the short and medium run, which is particularly important for housing markets (England, 2016). We find that property tax increases lead to lower house prices, which is evidence of capitalization into house values (Palmon andSmith, 1998, de Bartolomé andRosenthal, 1999).…”
Section: Introductionsupporting
confidence: 54%
“…The set of principles for the formation of the immovable property taxation system for individuals can be summarized as follows, depending on the number of references and significance (rank) ( Table II) The analysis of scientific literature [11], [12], [13] and the results of the expert survey has revealed several basic approaches used for the application of taxes on the immovable property of individuals in the world practice:…”
Section: A Findingsmentioning
confidence: 99%
“…They analysed previous studies regarding the capitalization of real estate tax into the value of real estate and found that Leed in his study from 1985 was the only one who did not find any evidence of the mentioned capitalization of real estate tax into the value of real estate. England (2016) reviewed the literature dealing with the taxpayers who actually bear the economic burden of a real estate tax levied on a rental property. He concluded that owners (landlords) can shift property tax onto renters (tenants), but only when renters are willing to pay for the goods and services offered by their local communities and financed by real estate tax (ibid).…”
Section: Prices Of Residential Real Estatementioning
confidence: 99%
“…Proučila sta predhodne študije o kapitalizaciji davka na nepremičnine v vrednost nepremičnine in ugotovila, da le Leed v svoji študiji iz leta 1985 ni našel dokazov o navedeni kapitalizaciji davka v vrednosti nepremičnine. England (2016) je proučil literaturo glede nosilcev davčnega bremena davka na nepremičnine, ki se oddajajo v najem. Prišel je do spoznanja, da lastniki nepremičnin lahko prevalijo davek na nepremičnine na najemnike, le ko so slednji pripravljeni plačati dobrine in storitve, ki jih ponujajo lokalne skupnosti in so financirane z davkom na nepremičnine (ibid).…”
Section: Cene Rezidenčnih Nepremičninunclassified